Drag Coefficient Constraints for Space Weather Observations in the Upper Thermosphere. Issue 5 (6th May 2022) - Bernstein, Valerie; Pilinski, Marcin
Abstract: The space weather research community relies heavily on thermospheric density data to understand long‐term thermospheric variability, construct assimilative, empirical, and semiempirical global atmospheric models and validate model performance. One of the challenges in resolving accurate thermospheric density data sets from satellite orbital drag measurements is modeling appropriate physical aerodynamic drag force coefficients. The drag coefficient may change throughout the thermosphere due to model dependencies on composition and altitude. As such, existing drag coefficient model errors and corresponding errors in orbit‐derived density data sets and models may be altitude and solar cycle dependent with greater errors at higher altitudes around 500 km near the oxygen‐to‐helium transition region. In this paper, inter‐satellite observed‐to‐modeled density comparisons at ∼500 km are evaluated to constrain drag coefficient modeling assumptions. Observed densities are derived from accelerometer data for the Gravity Recovery and Climate Experiment (GRACE) satellites and Two‐Line Element data for a set of compact satellites, while the NRLMSISE‐00 atmospheric model is used to obtain modeled densities and composition information. Density consistency results indicate that drag coefficient models with incomplete energy and momentum accommodation produce the most consistent densities, while the standard diffuse modeling approach may not be appropriate at these altitudes. Models with momentum accommodation between 0.5 and 0.9 and energy accommodation between 0.83 and 0.96 may be most appropriate at upper thermospheric altitudes. Modeling drag coefficients with diffuse gas‐surface interactions for the GRACE satellites could lead to errors in derived density of ∼25% and in‐track satellite orbit prediction uncertainty during solar maximum conditions on the order of kilometers. Plain Language Summary: The Earth's upper atmosphere exerts forces on satellites that can change their paths. It is critical to understand how these atmospheric drag forces work in order to measure atmospheric variability and predict satellite orbital paths in an increasingly crowded near‐Earth space. The atmospheric drag force depends on interactions between atmospheric particles and the surface of a satellite. Gas particles can impact a satellite surface and scatter in a variety of ways. Depending on the speed and direction of the scattered particles, the atmospheric drag force on a satellite can change. The appropriate type of scattering for atmospheric particles interacting with a satellite surface in orbit remains uncertain. In this work, the authors try to infer the nature of gas‐surface scattering by comparing atmospheric densities derived from orbital changes measured for satellites of different shapes. The density comparisons suggest that standard assumptions about surface scattering in orbit may not be appropriate, but rather assuming scattering that is less random may be better at upper altitudes near and above 500 km. Assuming the wrong scattering physics could lead to errors in densities derived from satellite orbital data of ∼25% and satellite orbit prediction variations of tens to hundreds of meters along the satellite track. Key Points: Drag coefficient errors lead to altitude‐dependent biases in thermospheric densities Drag coefficient model assumptions are constrained by evaluating multi‐satellite density consistency Aerodynamic drag modeling is improved near 500 km by assuming incomplete momentum accommodation